Initial Presentation of OCD and Psychosis in an Adolescent during the COVID-19 Pandemic - Nazeer, Sahana; Reddy, Abhishek (Case Reports in Psychiatry, 2022)
The COVID-19 pandemic is unparalleled in recent history when accounting for the true disease burden and dramatic impact on physical and mental health. Due to its infectious pathology, COVID-19 presents with a variety of symptoms including neuropsychiatric complications. Moreover, factors such as quarantine, social isolation, and fear of illness have negatively impacted the health of non-COVID-19 patients. There has been significant literature reporting new-onset psychiatric illness in all global populations including those without history of psychiatric illness. This report discusses an adolescent male without prior psychiatric history presenting with new onset symptoms of obsessive-compulsive disorder and psychosis in the context of COVID-19. There are considerable reports describing new-onset obsessive-compulsive disorder, albeit conflicting in terms of prevalence and exacerbations in the setting of COVID-19 in both adult and adolescent populations but limited reports of new-onset psychosis in those same populations and setting.